Metadata generation and consolidation within an ontology-based document management system. (2nd March 2009) - Mitschick, Annett; Meissner, Klaus
A central issue for the benefit and success of an ontology-based personal document management system is its capability to automatically model appropriate and valid document descriptions. The generation process primarily depends on the application context and should be customised accordingly. Furthermore, automatically generated information needs appropriate cleaning and consolidation to maintain a certain level of data quality. Therefore, this paper presents a semantic document management system which applies a stepwise knowledge modelling process. Our approach separately addresses the problems of general translation of diverse information sources, syntax check, normalisation and duplication and conflict handling, based on consecutive and configurable stages.